METHOD FOR PREDICTING THERAPEUTIC EFFECT OF PHARMACOTHERAPY IN TREATMENT OF SUBJECT WITH METASTATIC PROSTATE CANCER, KIT, ARRAY, AND BIOMARKER - SHIOTA Masaki; ETO Masatoshi (2024)
A method according to the present invention is a method for predicting the therapeutic effect of pharmacotherapy in the treatment of a subject with metastatic prostate cancer, wherein the pharmacotherapy includes at least one selected from among androgen deprivation therapy, androgen receptor deprivation therapy, and an anticancer drug, and said method includes a step for detecting the presence or absence of at least one single nucleotide polymorphism in the subject. Selon la présente invention, un procédé permet de prédire l'effet thérapeutique d'une pharmacothérapie dans le traitement d'un sujet atteint d'un cancer de la prostate métastatique, la pharmacothérapie comprenant au moins un médicament choisi parmi une thérapie de privation androgénique, une thérapie de privation des récepteurs androgéniques et un médicament anticancéreux, et ledit procédé comprend une étape de détection de la présence ou de l'absence d'au moins un polymorphisme mononucléotidique chez le sujet. 本発明の方法は、転移性前立腺癌対象の治療における薬物療法の治療効果を予測するための方法であって、上記薬物療法がアンドロゲン遮断療法、アンドロゲン受容体遮断療法及び抗がん剤から選択される少なくとも１つを含み、上記方法は上記対象における１種以上の一塩基多型の存在の有無を検出するステップを含む。